Migrant and the Impact to Social-Economic of Household at Plumbon, Polokarto Sub-District - Astuti, Wahyuni Apri (Universitas Muhammadiyah Surakarta, 1997)
This research was caried out in Plumbon district of Mojolaban and it was intended to find out demographyc characteristic and migrant social economy, way of mobility process, factor, and reason which affect mobility and social economy effect of mobility action to the migrant family. The applied method to research was surveying and the area of the research was selected purposively, respondent in the surveying amount to 60 which was collected at random out of 320 population. The research outcome shows that mobility agent include in the group of potential age i.e domination of age 22 â 44 groun amount 63,33 percent. Thier education are relatively low i.e amount to 83.33 percent graduated from grammer school and lower. Or if it is more detailed there are 43.33 percent that did not go to school and did not pass grammer school. The work of respondent are 65 percent as workers of factory and construction. Average income per mount of migrant is relatively low i.e Rp 121.417 â only 30 perecent of then do the side job. The reason is that they have no more time as their working hours is long i.e 48 working hours per week, beside a larger part of them have not special skill. Before mobility action their work in farming, it mean that thereÂ happened the mobility of working. Decision to realize the mobility emerged from respondents them selves and the main information workes of destination area is an informal one. The effecct of go back and forth mobility to the migrant family is their income improvement, if it is compared to their income before mobility, it includes the problem of providing food, clothing, and education.